Local government policy in the watershed management of cisadane river on Banten Province - Chika Putri Nuralifah; Syarifah Izzatul Maula; Ilham Aji Pangestu; Muhammad Mpu Samudra (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
River is the main source of water which is used to support the primary needed of surrounding community. One of these rivers is the Cisadane River, which is located in Tangerang. This study aims to find out how the Banten Provincial Government's policies are related to the management of the Cisadane River Basin Area. This research belongs to Normative Law research which has Prescriptive sight. The legal source of this study is obtain through the library research. This reseach used statute approach and case approach. Based on the results of research and discussion, showed that there is no policy related to the management of the Cisadane River Basin Area, neither in Tangerang City, nor in South Tangerang, nor in Tangerang Regency. The recommended solution that can be given is wether the Regional Governments in Banten Province, or South Tangerang, or Tangerang Regency, to legislate the Regional Policy related to the Management of the Cisadane River Basin Area. Second, optimizing the role of  surrounding community of the Cisadane River Basin Area in Banten Province for caring and maintaining enviromental hygiene, wether in the river or surrounding environment near to the river which can be minimized the impact of river pollution.